Impacts And Strategies for Handling Covid-19 In Indigenous People: A Scoping Review (Comprehensive Health Care, 2024)
The COVID-19 pandemic is a major health emergency that causes significant suffering and many deaths among indigenous people worldwide. During the pandemic, indigenous communities have higher rates of health problems than the general population. This review explores the impact and strategies for handling COVID-19. This scoping review aims to draw key concepts from the available literature that underpins a research area. The literature search was conducted on eight databases, namely PubMed, DOAJ, Science Direct, Cochrane, Wiley, ProQuest, and Garuda, in July-November 2022. The online search engine was Google, and the keywords for the search were "impact of COVID-19 in indigenous people". The results of this review are expected to provide a reference of strategic considerations to deal with the pandemic in indigenous people. These strategies should focus on improving digital skills, health literacy to combat misinformation, awareness of COVID-19 handling, the benefits of COVID-19 prevention, and compliance with health guidelines as well as on actively involving patients in health decisions.